Congenital granular cell epulis: A rare diagnosis - Sigdel, B; Baidya, R; Shrestha, P; Shrestha, S (Journal of Pathology of Nepal, 2011)
Congenital granular cell tumor is very rare and it arises from the gum pad of neonates. Surgery is required immediatly after birth as the tumor interfares with feeding and respiration. Although a benign tumor, it can create immense anxiety amongst the attending physician and family members. Its recognition is important so as to avoid over diagnosis leading to radical surgery. We report a case of congenital epulis arising from the maxillary alveolar ridge in a newborn female child, which was successfully excised and the diagnosis confirmed histologically. No tumor recurrence has been reported in the patient postoperatively. Keywords: Congenital; Epulis; Granular cell DOI: 10.3126/jpn.v1i1.4458 Journal of Pathology of Nepal (2011) Vol.1, 69-72